Perlindungan Hukum Bagi Pengguna Fintech Pinjaman Online (Lembaga Pengabdian Masyarakat Universitas Ichsan Gorontalo, 2024)
This research investigates legal aspects related to protection for fintech users in the context of online lending in Indonesia. The background includes the rapid development of the fintech industry and the increasing use of online lending, which has created a need to evaluate the effectiveness of existing legal protections. This research uses a combination approach of regulatory analysis, case studies, and interviews with relevant stakeholders. The literature review involves the concept of fintech, related regulations, and legal protection challenges that users face. Research methods include in-depth analysis of applicable regulations, case studies of user experiences, and interviews with representatives of financial institutions and supervisory authorities. The results of this research provide a better understanding of the rights and obligations of fintech users in the online lending environment. Key challenges include legal uncertainty and unethical practices by some service providers. The research also suggests steps for improvement, including increased regulation, increased transparency, and user education. Thus, this research provides a comprehensive view of legal protection for online lending fintech users in Indonesia and provides a foundation for further improvements in industry regulations and practices.